Nanocomposites: Conjugated Polyelectrolyte/Graphene Hetero‐Bilayer Nanocomposites Exhibit Temperature Switchable Type of Conductivity (Adv. Electron. Mater. 2/2017). (February 2017) - Brus, Viktor V.; Gluba, Marc A.; Mai, Cheng‐Kang; Fronk, Stephanie L.; Rappich, Jörg; Nickel, Norbert H.; Bazan, Guillermo C.
Abstract : V. V. Brus et al. report that the majority charge carriers in CPE‐PyrBIm4 /graphene heterobilayers can be dynamically changed from electrons to holes, and vice versa, within a temperature range of 60 °C. Doping mechanisms under consideration include charge transfer from electron‐rich structural units in the CPE‐PyrBIm4 backbone and/or field‐effect doping due to interfacial electrostatic effects from adjacent ionic functionalities, as described in article number 1600515.